Comparing the effect of different carbon sources on growth, blood parameters, immunity, and water quality in Nile Tilapia (Oreochromis niloticus) cultured in a biofloc system - Mai H. Hussien; Mohamed M. Zayd; Ahmed E. Elshafey; Malik M. Khalafalla; Mustafa Shukry; Mohamed Abdelmegeid; Lamiaa A. Okasha; Rabiha Seboussi; Mohamed H. Aboraya; Ahmed A. Elolimy (Aquaculture Reports)
Aquaculture faces significant challenges in maintaining water quality and fish health. This study evaluated the effects of different carbon sources on growth, immunity, and water quality in Nile tilapia (initial weight: 2.8 ± 0.002 g) cultured in a biofloc system over 90 days. Five treatment groups were tested, including a control group without carbon supplementation (T1) and groups supplemented with molasses (T2), vinasse (T3), starch (T4), or rice bran (T5). Results showed that molasses significantly improved (p < 0.05) growth performance, feed efficiency, and hematological parameters, suggesting enhanced oxygen-carrying capacity and immune function. Additionally, molasses increased glucose, triglycerides, and albumin levels, improving liver function and energy metabolism. Immune responses, including lysozyme activity, IgM levels, and phagocytic activity, were significantly enhanced in the molasses group. Antioxidant enzyme activity was higher, and oxidative stress indicators were lower in this group. Histological analysis revealed improved intestinal and gill morphology in fish reared on molasses. Water quality parameters, such as pH, dissolved oxygen, and total ammonia nitrogen, were positively affected by vinasse and starch. Gene expression analysis indicated molasses-influenced genes associated with stress response, antioxidant activity, inflammation, and growth. These findings suggest that molasses is a promising carbon source for biofloc systems, improving growth, health, and water quality in Nile tilapia aquaculture.